Level of Knowledge, Attitude, and Behavior of Pregnant Women in Giving Stimulation to the Fetus - Sari, Ika Novita; Andita Nugrahani (HM Publisher, 2022)
Educating children as early as possible must start from the time the child is in the womb. Biologically human life begins at the time of conception or fertilization as well as human biological development. This study aims to determine the knowledge, attitudes, and behavior of pregnant women in providing stimulation to the fetus. This research is an observational study with a cross-sectional design. The population is pregnant women more than 20 weeks who check their pregnancy at the Baloi Permai Health Center in September-November 2021. The sampling technique uses purposive sampling with a sample of 48 people. Collecting data using a questionnaire and analyzing it using the chi-square test. The results showed that there was no relationship between knowledge and behavior of giving stimulation to the fetus (p=0.563); Likewise, there was no relationship between attitude and behavior in giving stimulation to the fetus (p=1.00). This study concludes that there is no relationship between knowledge and attitudes regarding the behavior of pregnant women in providing stimulation to the fetus.